2015
DOI: 10.15678/znuek.2015.0938.0209
|View full text |Cite
|
Sign up to set email alerts
|

Zmiany siły powiązań i zmienności indeksów giełd światowych

Abstract: Zmiany siły powiązań i zmienności indeksów giełd światowych StreszczenieCelem opracowania jest identyfikacja i ocena zmian w kształtowaniu się indeksów giełdowych, a w szczególności zwrócenie uwagi na zmiany siły powiązania indeksów reprezentujących akcje spółek z różnych regionów geograficznych i krajów, a także zmiany zachodzące w zmienności tych indeksów. Przeprowadzona analiza dotyczyła porównania kształtowania się indeksów w czasie, wyodrębnienia podokresów oraz określenia zmian siły powiązań pomiędzy pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The previously conducted research on the development of the Polish options market highlighted the changes in the deviations of option prices from certain relations resulting from arbitrage. Based on the results obtained, it was found that the number and scale of these deviations clearly decreased, improving the quality of the arbitrage pricing of options [Węgrzyn 2010;2011]. In this context, it is worth assessing the effectiveness of dynamic hedging in current market conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The previously conducted research on the development of the Polish options market highlighted the changes in the deviations of option prices from certain relations resulting from arbitrage. Based on the results obtained, it was found that the number and scale of these deviations clearly decreased, improving the quality of the arbitrage pricing of options [Węgrzyn 2010;2011]. In this context, it is worth assessing the effectiveness of dynamic hedging in current market conditions.…”
Section: Introductionmentioning
confidence: 99%